Phleboliths in a vascular malformation within the parotid gland - Stephen Garry; Jessica Wauchope; Tom Moran; Stephen M. Kieran (Elsevier, 2022)
We present the unusual case of a 12-year-old girl who was referred to our department having presented with unilateral facial swelling and a hard lump related to the right cheek. Initial investigations failed to definitively diagnose the condition given the wide differential diagnosis. After Multi-Disciplinary Team discussion, the consensus was for the lesion to be excised via a superficial parotidectomy for diagnostic purposes, especially given that there was some concern due to the unusual appearance of it on imaging. Post-operative histology revealed a venous malformation with phlebolith formation within it. The 'clumping' together of the phleboliths gave rise to the unusual appearance on CT and MRI.